REPORT ON CURRENT ACTIVITIES RELATED TO THE BINGAMAN, MITCHELL AND STEVENS BILLS. - STUNTZ SM (Tufts Archival Research Center, 2007)
Report on efforts related to the Bingaman, Mitchell, and Stevens proposals in Congress. Includes discussion of different organizers against an increased cigarette excise tax and possible allies. Plans to target Governmental Affairs and Armed Services committee members in regards to a bill to restrict smoking in government buildings.